2013
DOI: 10.3389/fnhum.2013.00542
|View full text |Cite
|
Sign up to set email alerts
|

Type of gesture, valence, and gaze modulate the influence of gestures on observer's behaviors

Abstract: The present kinematic study aimed at determining whether the observation of arm/hand gestures performed by conspecifics affected an action apparently unrelated to the gesture (i.e., reaching-grasping). In 3 experiments we examined the influence of different gestures on action kinematics. We also analyzed the effects of words corresponding in meaning to the gestures, on the same action. In Experiment 1, the type of gesture, valence and actor's gaze were the investigated variables Participants executed the actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
3
11
1
Order By: Relevance
“…This result appears in agreement with our initial hypothesis, confirming the theory of neural signatures of affective experience [20,21,70], which postulates an increase of left-brain responsiveness according to positive stimuli, inducing an "approaching behavior", compared to negative ones, which provides an increase of right-brain responsiveness inducing an "avoidance behavior" [71].…”
Section: Discussionsupporting
confidence: 91%
“…This result appears in agreement with our initial hypothesis, confirming the theory of neural signatures of affective experience [20,21,70], which postulates an increase of left-brain responsiveness according to positive stimuli, inducing an "approaching behavior", compared to negative ones, which provides an increase of right-brain responsiveness inducing an "avoidance behavior" [71].…”
Section: Discussionsupporting
confidence: 91%
“…For instance, exploring a cooperative motor task, Quesque and Coello 38 reported that the spatial amplification of a grasp-to-place motor action was broader, resulting in a higher arm trajectory, when the partner's eye-level was set at a higher position. This result is in line with the key role of the gaze in the process of action understanding in social contexts [39][40][41][42][43] . Because of their social value, the spatio-temporal variations of object-directed motor actions are also thought to serve as crucial cues for an observer to identify the agent's social goal [44][45][46] .…”
Section: The Combined Effects Of Motor and Social Goals On The Kinemasupporting
confidence: 85%
“…Even if speculative, this interpretation is supported by two kinds of evidence. First, different studies demonstrated that eye-related cues are spontaneously considered when acting with a partner (De Stefani, Innocenti, Secchi, Papa, & Gentilucci, 2013;Ferri et al, 2011;Innocenti et al, 2012;Quesque & Coello, 2014). Second, recent works have shown that humans may use others' pupil changes to produce adaptive responses, without any training, when explicitly informed about their importance (Naber, Stoll, Einhäuser, & Carter, 2013) but also spontaneously in the absence of any instruction (Brambilla, Biella, & Kret, 2018;Kret & de Dreu, 2017;Kret et al, 2015;Van Breen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%